THE SOLAS VGM AND MARITIME SHIPPING: COMPARATIVE STUDY AND ORIGINAL FINDINGS (Perner's Contacts, 2018)
The International Maritime Organization (IMO) amended the Safety of Life at Sea (SOLAS) Convention, Chapter 6, Part A to include a condition that all full containers loaded onto a vessel for export require a certified weight confirmation titled verified gross mass (VGM) in 2014. The VGM requirement became effective in Jla 2016 for the IMO member countries that signed the SOLAS Convention of 1974 with leaving the details of its implementation at their national law domain. The paper briefly deals with the implementation process of VGM in selected European Union member countries while being improved by an initial review of trade press articles, followed by an survey among shippers, freight forwarders and ocean carriers. Based on the data, the paper identifies the expected challenges and costs related to the SOLAS VGM adoption for container exports that the companies have to face once doing business.
Keywords: Intermodal Transport, Container, SOLAS VGM